Density Functional Theory for Polymer Phase Separations Induced by Coupling of Chemical Reaction and Elastic Stress. Issue 1 (18th November 2021) - Oya, Yutaka; Kikugawa, Gota; Okabe, Tomonaga; Kawakatsu, Toshihiro
Abstract: A density functional theory is applied to phase separation dynamics influenced by crosslinking reactions in dense polymer solutions. The crosslinking reaction is modeled by a change from non‐crosslinked polymers comprising transient network (TN) to crosslinked polymers participating in the percolated permanent network (PN). Deformed TN polymers are considered to relax to the isotropic equilibrium state according to the Maxwellian linear viscoelastic constitutive equation, which is used in the modeling of viscoelastic phase separations. The PN is modeled by a linear elastic constitutive model. When TN polymers are taken into the PN by crosslinking reaction, the instantaneous deformation of the TN polymers are frozen, and such frozen deformations are accumulated as time goes on. A series of simulations is performed using this model, so that two specific features of the viscoelastic and reactive phase separation are obtained, i.e., 1) two‐stage phase separation process that leads to a domain structure with two different characteristic length scales, and 2) fixing the phase‐separated structure before reaching the macrophase separation. Abstract : A density functional theory is applied to phase separation dynamics influenced by crosslinking reactions in dense polymer solutions. The crosslinking reaction is modeled by a change from non‐crosslinked polymers comprising transient network to crosslinked polymers participating in the percolated permanent network. The elasticity due to the crosslinked polymers induces the two‐stage phase separation with two different characteristic length scales.